EXPERIENCES OF EXPRESSING SOCIAL JUSTICE IN NON-FORMAL ADULT EDUCATION - Zubrickienė, Ilona; Anužienė, Birutė (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
Social justice in education is a research area aimed at providing equal opportunities for everybody to participate in the educational system. Research in the field of social justice rather focuses on formal education, in which the perception of the social justice concept depends on the attitude framed by the state – it is inseparable from the form of governance, the set of basic principles prevailing in society, as well as from the historical and cultural context. On the contrary, non-formal adult education, as a relatively convenient and most accessible form of adult education to upgrade or acquire new skills, involves occasional studies of these service providers in terms of social justice. It is also limited to the generalised perception of this phenomenon and, usually, to the contexts of its expression that are not always regulated by the state. Therefore, it is not clear how non-formal adult education addresses the problem of perceiving and expressing the concept of social justice, what role the state might play in ensuring social justice for adults in lifelong development and acquisition of new skills. The article raises the following problematic questions: How do adults perceive and experience social justice when participating in and engaging in non-formal adult education? How and in what ways does social justice exist in non-formal adult education? The aim of the article is to show the authentic experiences of study participants, by identifying the concept of social justice and expressions thereof in non-formal adult education. The results of the study demonstrate the controversy of the concept of social justice. This helped to confirm that there is no single definition of social justice that would be acceptable in all contexts of education. The following key forms of expression of social justice were pointed out by the study participants: equal opportunities, access, non-compliance of non-formal adult education services with participants’ learning needs, goals, and objectives. This has revealed a partial aspect of implementing social justice in non-formal adult education.